2023
DOI: 10.5194/acp-23-8553-2023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of microphysics and dynamics in a warm conveyor belt simulated with the ICOsahedral Nonhydrostatic (ICON) model

Abstract: Abstract. Warm conveyor belts (WCBs) produce a major fraction of precipitation in extratropical cyclones and modulate the large-scale extratropical circulation. Diabatic processes, in particular associated with cloud formation, influence the cross-isentropic ascent of WCBs into the upper troposphere and additionally modify the potential vorticity (PV) distribution, which influences the larger-scale flow. In this study we investigate heating and PV rates from all diabatic processes, including microphysics, turb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…The detailed analysis of microphysical processes along a WCB revealed that condensational growth of cloud droplets and vapour deposition on frozen hydrometeors each contributed ∼ 10 K to the total latent heating (Joos and Wernli, 2012). The dominance of these two processes, identified in a simulation with 14 km grid spacing, a onemoment microphysics scheme, and offline trajectories, has recently been confirmed by Oertel et al (2023a), who investigated microphysical processes along the WCB of the NAWDEX IOP2 cyclone Vladiana, in a convection-permitting ICON simulation with two-moment microphysics and online trajectories. Considering these two microphysical processes, the parameterization of depositional growth is clearly more uncertain in weather and climate models (e.g., due to the treatment of supersaturation).…”
Section: Diabatic Outflows and Forecast Errorsmentioning
confidence: 80%
“…The detailed analysis of microphysical processes along a WCB revealed that condensational growth of cloud droplets and vapour deposition on frozen hydrometeors each contributed ∼ 10 K to the total latent heating (Joos and Wernli, 2012). The dominance of these two processes, identified in a simulation with 14 km grid spacing, a onemoment microphysics scheme, and offline trajectories, has recently been confirmed by Oertel et al (2023a), who investigated microphysical processes along the WCB of the NAWDEX IOP2 cyclone Vladiana, in a convection-permitting ICON simulation with two-moment microphysics and online trajectories. Considering these two microphysical processes, the parameterization of depositional growth is clearly more uncertain in weather and climate models (e.g., due to the treatment of supersaturation).…”
Section: Diabatic Outflows and Forecast Errorsmentioning
confidence: 80%
“…WCBs are challenging to predict due to the small‐scale cloud‐microphysical processes associated with their air stream (Oertel et al., 2020; Oertel, Miltenberger, et al., 2023) thereby facing both intrinsic limits of predictability and problems in an accurate representation in models. In a previous study, we could show that skillful predictions of WCBs in current numerical weather prediction (NWP) models are possible only until around 8–10 days (Wandel et al., 2021).…”
Section: Introductionmentioning
confidence: 99%